The Evaluation of Daylighting Performance in The University Classroom. An Experimental Study - Muhammad Syarif Hidayat (Department of Architecture Universitas Muhammadiyah Jakarta, 2022)
To obtain natural light in the room course need aperture wide. However, it will cause the room to become hot because radiation also can come in. To reduce the radiation, the curtains are used to reduce such radiation. This resulted in the lighting level in the classroom decreases. When this is the case, then artificial lighting is needed. This study aims to optimize natural and artificial light in classrooms that use a curtain. The results showed that the level of natural lighting that can reach all of the space obtained by opening all the curtains. At the point of measuring in the front (near the board) reached 284 to 325 lux. However, on the side of the window gets very high light from 3100 to 3340 lux (TU 10, 11, and 12). If the blinds partially open (50%) the light only reaches the middle of the room (TU 7,8,9). The use of lights is not a lot of role because of the level of exposure of the lamp not according to the standard